Psychological investigation of the novel “A stone on a grave (Jalal Al-e-Ahmad, 1980)” - H Kaviani; AS Mousavi (JRI, 2001)
Jalal Al-e-Ahmad, a hard working contemporary novelist, in one of his writings, has made an autobiography about a problem, which had preoccupied his minds and life for many years. This was his infertility. In this book, the author probes the problem from the beginning of its appearing; his trials for solving it, eventual excitedly reactions of it, and compatibility with being “childlessness”. Memories have been designed as form of a novel. In research work, there is always, this possibility that, a quantitative “approach” cause to deprive us from some “qualitative”. May be psychological investigation of some novels specially those, which deal with “problem” of author, could fill this emptiness. This matter is the goal of this article for psychological investigation of infertility.
Keywords: Jalal Al-e-Ahmad, Psychological analysis, Infertility